Propriedades de concretos produzidos através da utilização de agregados reciclados de concreto - Pelissari, Viviane (2016)
The recycling of waste is an option to minimize the environmental impact of the significant amount of waste generated by production activities in the construction segment. Thus, the aim of this study is to evaluate the use of recycled coarse aggregate concrete (ARC) to replace the natural coarse aggregate (AGN) for the production of concrete with compressive strength of 30 MPa. The experimental program began with physical and particle size characterization of the recycled coarse aggregate concrete (ARC), and for comparison with the properties of natural coarse aggregate (AGN). Based on the knowledge of these properties, the next step was the production of concrete. Different procedures to reduce the effect of absorption of water by recycled concrete aggregate at the fresh state were studied. Also it was evaluated the effect of using different amounts (0, 10%, 20%, 50% and 100%) replacement of the natural coarse aggregate for concrete recycled coarse aggregate in to the properties of concrete at the fresh state and at the hardened state. Although it has been verified a decrease in the compressive strength values in relation to the reference concrete (without the presence of ARC), for all AGN replacement percentages by ARC was reached the value specified compressive strength (30 MPa). With regard to the modulus of elasticity and splitting tensile strength, it was found that the reduction in results intensifies with increasing percentage of ARC incorporated into the mixture. The values recorded for water absorption, in turn, gradually increased in proportion to the amount of the ARC.